OGBN P18 Laparoscopic Deroofing of a Liver Cyst. (7th December 2022) - Bradley, Alison; Kostalas, Marcos; Bowling, Kirk; Andrews, Stuart
Abstract: Background: Laparoscopic deroofing is considered to be part of standard practice for simple nonparasitic liver cysts. Methods: This "how to" video demonstrates an approach to the laparoscopic deroofing of a large, nonparasitic liver cyst. After the placement of umbilical, epigastric and a working right upper quadrant port, the cyst is aspirated. This allows easier handling of the cyst. A cystostomy is then created and a LOTUS or Harmonic scalpel is used to cut thru the cyst wall.Further suctioning of the cyst contents allows the cyst to collapse which facilitates handling of the tissue. Complete resection of the cyst can be achieved by dissecting close to the cyst wall which is then placed into an endobag prior to removal. It is important to ensure good haemostasis at the liver. Omentum may be placed in larger cavities to reduce dead space and prevent fluid collection. Results: This patient made a good postoperative recovery and cytology and histology confirmed benign cyst. Conclusions: This video demonstrates one approach to the laparoscopic deroofing of a large, simple, nonparasitic liver cyst.